Pengaruh Beban Pajak Tangguhan, Kebijakan Dividen dan Ukuran Perusahaan terhadap Manajemen Laba (Perusahaan Sektor Consumer Non-Cyclicals yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2019 -2023) - Silaban, Martua Uli; Romadhina, Anggun Putri (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
Earnings management remains a critical concern in financial reporting, particularly within companies operating in essential sectors where transparency is vital. This study investigates the influence of deferred tax expense, dividend policy, and firm size on earnings management practices in consumer non-cyclicals companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. The research aims to address inconsistencies in previous findings by offering empirical evidence from a focused industrial context. Using a purposive sampling method, 11 companies were selected based on specific criteria, resulting in 55 observations over five years. Earnings management was measured using the scaled earnings changes method, while deferred tax expense was calculated as a ratio of deferred tax to total assets. Dividend policy was proxied by the dividend payout ratio, and firm size was measured using the natural logarithm of total assets. Panel data regression analysis was conducted using EViews 13, with model selection based on Chow and Hausman tests. The findings reveal that, simultaneously, deferred tax expense, dividend policy, and firm size significantly affect earnings management. However, individually, only firm size has a significant impact, suggesting that larger companies are more likely to engage in earnings management due to operational complexity and external pressure. These results offer insights for regulators and investors to improve monitoring mechanisms in financial reporting practices.